MITHILA'S 'FAKDE' ENCOMPASSES VARIOUS COLORS OF LIFE: जीवन के विविध रंगों को समेटे हैं मिथिला के ‘फैकड़े‘ - mishra, Niraj kumar (International Journal of Research -GRANTHAALAYAH, 2020)
English: Loktokis are particularly associated with the social life of a particular region and the language and culture of the region. Loktokis are the treasures of empirical knowledge. The facts that humans have interviewed through the ages are published through them. These are the sources of long-felt knowledge. The main objective is to publish a largely realized wisdom in a concise form. If the ideology of a caste has flowed from centuries, it is necessary to study the ethos of that caste. Hindi: लोकोक्तियाँ किसी क्षेत्र विषेश के सामाजिक जीवन और वहाँ की भाषा और संस्कृति से खास तौर से जुड़ी होती हैं। लोकोक्तियाँ अनुभवसिद्ध ज्ञान की निधि हैं। मानव ने युग-युग से जिन तथ्यों का साक्षात्कार किया है, उनका प्रकाशन इनके माध्यम से होता है। ये चिरकालीन अनुभूत ज्ञान के सूत्र हैं। समास रूप में चिरसंचित अनुभूत ज्ञान राषि का प्रकाशन इसका प्रधान उद्देश्य है। शताब्दियों से किसी जाति की विचारधारा किस ओर प्रवाहित हुई है, यदि इसका दिग्दर्शन करना हो तो उस जाति की लोकोक्तियों का अध्ययन आवश्यक है।